Analysis of Learning Outcome-based Teacher Training Programmes – Development Experiences in Hungary - Pesti, Csilla; Rapos, Nóra; Nagy, Krisztina; Bohán, Mariann (Acta Paedagogica Vilnensia, 2017)
In the past decade, teacher education has changed twice in Hungary, and the following question arises in this context: what different patterns can be observed in the teacher education institutions’ pedagogical and psychological modules regarding the learning outcome-based training programme development? To this end, a comparative document analysis has been conducted on the training program documents provided by 7 Hungarian universities. The results have revealed a strong internal coherence only between the goals and the contents of the courses in their descriptions; therefore, besides the professional discourse, it would be important that the learning outcomes are not only formally indicated in these documents.